2021
DOI: 10.1007/s13300-020-00996-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of Telemedicine in Diabetes Care: The Time is Now

Abstract: The utilization of telemedicine solutions to reduce outpatient clinic visits and visits to physicians' offices, thus saving financial and personal resources as well as time, has gained substantial importance in recent years. The COVID19 pandemic has made it necessary to abruptly adjust outpatient care methods in various medical settings that needlessly require consultations in person to monitor and change the disease management of patients in specific risk groups. People with diabetes represent a vulnerable po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 45 publications
1
54
0
4
Order By: Relevance
“…Younger diabetes patients were more interested in utilizing apps and had a greater desire and confidence in doing so in the future. Diabetic patients with a higher education (graduate) had a more favorable attitude toward and confidence in using apps, and they used their phones and the internet more frequently [ 31 , 32 ]. These findings might be explained by the fact that patients with a higher level of education have better reasoning and critical thinking abilities than others, resulting in greater judgement and trust in mobile health devices.…”
Section: Discussionmentioning
confidence: 99%
“…Younger diabetes patients were more interested in utilizing apps and had a greater desire and confidence in doing so in the future. Diabetic patients with a higher education (graduate) had a more favorable attitude toward and confidence in using apps, and they used their phones and the internet more frequently [ 31 , 32 ]. These findings might be explained by the fact that patients with a higher level of education have better reasoning and critical thinking abilities than others, resulting in greater judgement and trust in mobile health devices.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, patients with diabetes reported a high perceived quality of the TMTA services, thus confirming the positive experience of this category of patients with telemedicine and teleassistance during the health crisis. Plenty of literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14] supports the crucial role that TMTA services have played in assisting or substituting in-person visits during the most critical phases of the COVID-19 pandemic. Unpublished data from a survey conducted by AMD in collaboration with the Italian Ministry of Health on 225 diabetology centers showed that, during the first wave of the pandemic in Italy, it was not possible to provide care to more than half of the patients with diabetes who should have benefitted from follow-up visits during the period considered.…”
Section: Discussionmentioning
confidence: 99%
“…retinopathy screening, foot ulcer assessment), personal health records sharing, and interventions (e.g. lifestyle interventions, therapy control and adjustment) [11][12][13]. However, the implementation of TMTA services for diabetes care has been greatly accelerated by the outbreak of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A simple telediabetology could be developed, including observation or screening, documentation and intervention. [ 39 ] For observation or screening the scenario is to prepare the hotline services that reachable by patients with diabetes for critical decision making or clinic appointment. Regular visit could be replaced by private consultation through video mode to increase trust between patients and health care providers.…”
Section: Discussionmentioning
confidence: 99%